His words replete with guile, Into her heart too easie entrance won - Jean-Jacques LECERCLE (E-REA)
It all starts with the analysis of three famous seduction scenes (Eve seduced by the serpent, Lady Anne by the future Richard III and the people of Rome by Mark Antony). This allows a detailed account of Sandrine Sorlin’s “principle of illusion”, in contradistinction with straightforward manipulation. This development involves an analysis, after Klemperer and Sternberger, of Hitler’s discursive charisma, and it ends in the formulation of three theories of seductive discourse, one dystopian (Barthes’s “linguistic fascism”), another neutral (derived from Althusser’s theory of interpellation) and the last utopian (the seduction of literary incipit, illustrated by the first page of Martin Chuzzlewit and the first sentence of Joyce’s The Dead).